The level of schemed thinking and their relationship with some basic skills in football game. - grine , walid (sports creativity, 2025)
The study aims at recognizing the attecked schematic thinking level and its relation with some basic skills like rolling , scoring and handling, this study is conducted on sample U19 football players in Biskra consist of (42), to collect data and information, the discriptive approach form of correlated relation method is applied along with skillful tests relatted to the skills under examination, after statistical processing, it is found that the football players of the sample have an average level of attacked schematic thinking. Moreover, there is a relation between the attacked schematic thinking and rolling skills, the scoring skill and the handling skill.